(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In The Great Gatsby, alienation is connected with the collapse of the American dream, the dominance of wealth, moral indifference and the inability of the hero to find genuine human intimacy in a materialistic environment. In Uzbek novels of the Independence period, alienation is represented through the crisis of transition, social instability, moral uncertainty and the individual’s search for spiritual balance in a changing society. The article argues that although Fitzgerald and Uzbek writers belong to different literary, historical and cultural contexts, their novels reveal a common artistic problem: the individual becomes alienated when society loses moral harmony and replaces human values with material, social or ideological ambitions. The comparative analysis demonstrates that the poetics of alienation in these novels is expressed through narrative structure, symbolic details, inner conflict, social contrast and the opposition between external success and internal emptiness.